Escravidão e violência: uma história de resistência negra na província de Sergipe (1850-1888) - Santos, Josefa Eliene dos (2024)
In dialogue with the historiography on slavery in Sergipe, this dissertation discusses the rebellion of slaves against the violence of the slavery system in the Province of Sergipe, based on criminal proceedings inventoried in the General Archive of the Judiciary. Our work proposes to deconstruct the myth of the good master and the existence of a mild captivity with harmonious social relations, which were constructed throughout the 19th century, since the work Memorial Sobre a Capitania de Sergipe (1808), by the cleric Dom Marcos de Souza and reproduced by other authors in the 20th century. The fundamental characteristic of the slavery system was violence, which served both for social control and maintenance of order, and as an instrument of slave resistance, mainly in crimes committed by captives, in order to combat excesses and maintain acquired benefits. In the records of homicides and attempted homicides of blacks and whites, we studied the resistance of enslaved people in the province of Sergipe in the context of the social and penal transformations of the second half of the 19th century. In these processes, violence against blacks was treated as synonymous with aggression and cruelty, while oppression against whites was justified as necessary to maintain social order. Based on this documentary corpus, we established a dialogue with historiography, which, since the 1970s, has deconstructed the image of soft slavery, recovering the enslaved as subjects of social transformations and agents of their liberation. Thus, the process of transforming the act into a report, whether it is a police or judicial source, allows us to remove slavery from a harmonious representation and place it within the realm of conflict and unpredictability of history.